Gating Harmonization Guidelines for Intracellular Cytokine Staining Validated in Second International Multiconsortia Proficiency Panel Conducted by Cancer Immunotherapy Consortium (CIC/CRI). Issue 1 (2nd November 2020) - Price, Leah S.; Adamow, Matthew; Attig, Sebastian; Fecci, Peter; Norberg, Pamela; Reap, Elizabeth; Janetzki, Sylvia; McNeil, Lisa K.
Abstract: Results from the first gating proficiency panel of intracellular cytokine staining (ICS) highlighted the value of using a consensus gating approach to reduce the variability across laboratories in reported %CD8 + or %CD4 + cytokine‐positive cells. Based on the data analysis from the first proficiency panel, harmonization guidelines for a consensus gating protocol were proposed. To validate the recommendations from the first panel and to examine factors that were not included in the first panel, a second ICS gating proficiency panel was organized. All participants analyzed the same set of Flow Cytometry Standard (FCS) files using their own gating protocol. An optional learning module was provided to demonstrate how to apply the previously established gating recommendations and harmonization guidelines to actual ICS data files. Eighty‐three participants took part in this proficiency panel. The results from this proficiency panel confirmed the harmonization guidelines from the first panel. These recommendations addressed the (1) placement of the cytokine‐positive gate, (2) identification of CD4 + CD8 + double‐positive T cells, (3) placement of lymphocyte gate, (4) inclusion of dim cells, (5) gate uniformity, and (6) proper adjustment of the biexponential scaling. In addition, based on the results of this proficiency gating panel, two new recommendations were added to expand the harmonization guidelines: (1) inclusion of dump channel marker to gate all live and dump negative cells and (2) backgating to confirm the correct placement of gates across all populations. © 2020 International Society for Advancement of Cytometry